Association between haematopoietic stem cell transplantation and distress - anxiety - depression - Kiropoulou, Asimina; Polikandrioti, Maria (Health & Research Journal, 2019)
Introduction: In recent decades, more and more studies indicate that haematopoietic stem cell transplantation triggers numerous mental disorders to the haematological patient. Aim: The aim of the present study was to review the literature on the occurrence of mental disorders, such as distress, anxiety and depression in hematological patients undergoing haematopoietic stem cell transplantation. Material-Method: The method of this study included research of the literature from reviews and researches in «pubmed» and «google scholar» databases, which referred to the association between haematopoietic stem cell transplantation and the occurrence of psychiatric disorders. The search covered the period 2000-2015. Results: According to the literature, the process of bone marrow transplantation is often associated with the onset of distress, anxiety and depression in patients, which may adversely affect their compliance to treatment, the outcome of the procedure, and survival rates. However, many patients are reluctant to express their feelings, and are not questioned by health professionals about their mental worries. As a result, the psychological aspects of their disease may be underestimated. Furthermore, in this group of patients that display numerous physical symptoms, is difficult to diagnose and treat psychological aspects because they often mimic those of their disease. Conclusions: The systematic appraisal of distress, anxiety and depression should be an integral part of the treatment of hematological patients undergoing transplantation.